FATORES DETERMINANTES DA METILAÇÃO DO GENE NR3C1 EM USUÁRIOS DO SISTEMA ÚNICO DE SAÚDE NO MUNICÍPIO DE ALEGRE/ES - Pinheiro, Julia de Assis (2020)
The NR3C1 gene is related to psychosocial stress and has the promoter region regulated by methylation in the face of environmental exposure. The literature refers to methylation in this gene as related to gestational hunger, war stress and depression. Thu